Community participation and its role in the quality of life among the elderly - Rabah, Sayah (The International tax journal, 2025)
This scientific article aims to discuss the reality of community participation among the elderly and to determine their level of life satisfaction. It does so by shedding light first on the concept of community participation, its dimensions, and the conditions for its realization, and then by identifying the role of civil society organizations in promoting community participation in Algeria. Studying this issue, with its various forms of collective action, requires focusing on the social frameworks that support participants—particularly the elderly—and assessing their capacity to shape patterns of participation. This approach helps to identify the variables that define the activity of social forces in Algeria. Furthermore, the activation of community participation is closely linked to social structure and social awareness, which this article seeks to highlight. The paper also aims to define the concept of quality of life, its indicators, and its measurement tools.